Involvement of T-complex protein 1-ring complex/chaperonin containing T-complex protein 1 (TRiC/CCT) in retrograde axonal transport through tau phosphorylation - Chen, Xu-Qiao (Neural regeneration research, 2019)
Either overexpression of a single or all eight subunits (CCT1-8) or treatment of the substrate-binding apical domain of yeast CCT1 (ApiCCT1) prevented mutant Huntingtin aggregation and improved cellular and neuronal functions (Zhao et al., 2016). [...]the average retrograde velocity (the relative velocity calculated from moving time with pause time included) in CCT5-expressing neurons was significantly faster than observed in control neurons. [...]an overload of tau in axons may induce an adverse effect on axonal transport (Wang and Mandelkow, 2016). Furthermore, almost all the transfected CCT5 subunits formed a complex in which tau was absent (Chen et al., 2018b). [...]it is possible that the effect of CCT5 on tau phosphorylation requires an oligomeric complex that is either self-assembled by transfected CCT5 or assembled by CCT5 with other endogenous CCT subunits.